Financing Terrorism - Pieth, Mark. (Springer Netherlands, 2002)
In declaring the war against terrorism President George W. Bush also declared war on the financing of terrorism. The call to arms has been complemented by a concerted effort world-wide to track down and freeze the assets of suspected terrorists and financial institutions have risen to these challenges over the last year contributing their expertise gathered mostly through techniques to combat money laundering. In this book bankers, regulators and academics pose a variety of questions from their individual perspectives: To what extent are new laws really new? What can financial institutions realistically contribute to the suppression of terrorist financing? Can individual rights be protected in these circumstances? These questions are analysed by experts who come up with some thought provoking answers.